A Proposed Middle-Range Theory of Nursing in Hypertension Care. (22nd February 2018) - Drevenhorn, Eva
Abstract : Nursing in hypertension care comprises counselling about lifestyle changes, blood pressure measurement, and being a translator for the physician. For the patient, changing lifestyle means performing self-care. As not much in the form of research and guidelines for nurses is available, a middle-range theory of nursing in hypertension care was developed to guide nurses in their practice, in order to improve the nursing of patients and design studies for investigating nursing in hypertension care. Concepts are presented related to the patient (attitude and beliefs regarding health and sickness, autonomy, personality and traits, level of perceived vulnerability, hardiness, sense of coherence, locus of control, self-efficacy, and access to social support and network) and the nursing (applying theories and models for behavioural change in the consultation and using counselling skills, patient advocacy, empowerment, professional knowledge and health education, and supporting the patient). Then the concepts related to the consultation (communication, shared decision-making, concordance, coping, adherence, and self-care) are integrated with Orem's theory of nursing. Clinical and research implications of the theory are discussed.